2016
DOI: 10.1039/c5cp04556h
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed EPR characterization of HIV-1 protease conformational sampling and inhibitor-induced population shifts

Abstract: The conformational landscape of HIV-1 protease (PR) can be experimentally characterized by pulsed-EPR double electron-electron resonance (DEER). For this characterization, nitroxide spin labels are attached to an engineered cysteine residue in the flap region of HIV-1 PR. DEER distance measurements from spin-labels contained within each flap of the homodimer provide a detailed description of the conformational sampling of apo-enzyme as well as induced conformational shifts as a function inhibitor binding. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 109 publications
(340 reference statements)
1
32
0
Order By: Relevance
“…The overall structure of the HIV-1 protease is rigidified upon Ab/RIT binding or upon mutation. HIV-1 protease is widely studied by techniques including nuclear magnetic resonance (NMR) [36][37][38][39][40] , X-ray crystallography [41][42][43] , electron paramagnetic resonance (EPR) 17,20 , and molecular dynamics simulations 23,35,44,45 . NMR experiments suggested large scale flap dynamics of unliganded form of HIV-1 protease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall structure of the HIV-1 protease is rigidified upon Ab/RIT binding or upon mutation. HIV-1 protease is widely studied by techniques including nuclear magnetic resonance (NMR) [36][37][38][39][40] , X-ray crystallography [41][42][43] , electron paramagnetic resonance (EPR) 17,20 , and molecular dynamics simulations 23,35,44,45 . NMR experiments suggested large scale flap dynamics of unliganded form of HIV-1 protease.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that CDRs of the antibody are highly flexible and they adjust themselves to accommodate different conformations of the same epitope sequence (P36-45) in peptide and protein antigens. Thus, our study explained the cross-reactivity of P36-45 peptide and protease with antibody 12 .There is a large diversity in the flap conformations in the unbound state, fluctuating between the closed, semi-open, and wide-open conformations [13][14][15][16][17] . In the closed/semi-open conformation, the catalytic site is covered by two flaps, and thus restricts the entry of most of the ligands.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The development of selective and non-perturbing molecular probes is vital for understanding the complex interactions of biological systems with biomolecules on surfaces.N itroxide radical spin labels for electron paramagnetic resonance (EPR) spectroscopy are an effective way to monitor protein dynamics. [1][2][3] By using nitroxide spin labels,binding of various enzymes, [4] lectins, [5] RNA, [6] and other bio-macromolecules may be observed and quantified with EPR, offering opportunities to understand interfacial recognition at surfaces, including how receptor density on cell surfaces affects multivalent interactions with proteins.…”
mentioning
confidence: 99%
“…[1][2][3] By using nitroxide spin labels,binding of various enzymes, [4] lectins, [5] RNA, [6] and other bio-macromolecules may be observed and quantified with EPR, offering opportunities to understand interfacial recognition at surfaces, including how receptor density on cell surfaces affects multivalent interactions with proteins.…”
mentioning
confidence: 99%